2002
DOI: 10.1152/ajpregu.00768.2001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of afferent, central, and efferent components of the baroreceptor reflex in mice

Abstract: Studies of genetically modified mice provide a powerful approach to investigate consequences of altered gene expression in physiological and pathological states. The goal of the present study was to characterize afferent, central, and efferent components of the baroreceptor reflex in anesthetized Webster 4 mice. Baroreflex and baroreceptor afferent functions were characterized by measuring changes in renal sympathetic nerve activity (RSNA) and aortic depressor nerve activity (ADNA) in response to nitroprusside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 44 publications
2
75
1
Order By: Relevance
“…Nearly all values of cardiovascular parameters obtained in mice are well within the range predicted by allometric scaling equations from rats and humans (15). The baroreceptor reflex (22) and the regulation of fluid and electrolyte homeostasis by the renin-angiotensin system (8), two of the major blood pressure regulating systems (30,32), seem to function in a very similar fashion as in larger mammals.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Nearly all values of cardiovascular parameters obtained in mice are well within the range predicted by allometric scaling equations from rats and humans (15). The baroreceptor reflex (22) and the regulation of fluid and electrolyte homeostasis by the renin-angiotensin system (8), two of the major blood pressure regulating systems (30,32), seem to function in a very similar fashion as in larger mammals.…”
supporting
confidence: 60%
“…Most relevant techniques and experimental protocols to assess cardiovascular function have now been adapted to the small size of the mouse. These include chronic measurements of blood pressure (6,14,21,23) and cardiac output (16), the analysis of the different components of the baroreceptor reflex (22), and renal function and balance studies (21). Many aspects of the murine cardiovascular system-anatomic and physiological-are identical to larger mammals.…”
mentioning
confidence: 99%
“…CIH significantly accelerated the HR responses to electrical stimulation at lower frequencies (P Ͻ 0.05). At high frequencies (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), no difference was found between groups.…”
Section: Cih Accelerated the Hr Response To Electrical Stimulation Ofmentioning
confidence: 88%
“…Previously, Ma et al (31) found that pentobarbital sodium selectively impaired reflex control of the HR and did not exert a major effect on reflex control of peripheral sympathetic nerve activity or vascular resistance in mice. Furthermore, the baroreflex response (sympathoexcitation) of renal sympathetic nerve activity (RSNA) during hypotension is largely attenuated, but baroreflex RSNA response (sympathoinhibition) during PE injection is rather complete in pentobarbital-anesthetized mice (31). Consistent with these observations, sympathoexcitation of RSNA during MABP decrease is dramatically blunted in inactin-anesthetized rats, but sympathoinhibition of RSNA to the increase of MABP seems similar to that in conscious rats (33,34).…”
Section: Functional and Anatomical Implications Of Augmented Hr Respomentioning
confidence: 94%
“…A technical limitation to be considered in interpreting the peripheral measures of HF is that the hemodynamic measurements and blood sampling were performed under pentobarbital anesthesia, Pentobarbital anesthesia is known to blunt sympathetic and cardiovascular responses, 50 and that effect may have diminished the differences between groups. Nonetheless, significant differences were observed in hemodynamics measurements and in plasma NE values in MI versus SHAM rats, and in MI rats treated with AdIL-10 versus ␤Gal.…”
Section: Discussionmentioning
confidence: 99%